Evaluation of in-vivo antiarthritic potential of methanolic extract of Costus speciosus rhizome - Chandra Kala, Syed Salman Ali, Mohd. Abid, U S Sharma, Najam Ali Khan (Journal of Applied Pharmaceutical Science, 2015)
Objective: To evaluate anti-arthritic potential of methanolic extract of rhizome of Costus speciosus Koen. Methods: The powdered drug was extracted with 80% methanol. The crude extract was subjected to phytochemical investigation and was evaluated for its anti-arthritic potential by freund’s complete adjuvant induced arthritis model in adult wistar albino rats. Determination of different parameters like arthritic score, arthritic index, paw thickness, body weight, and pain, altered liver enzymes and biochemical estimation like, nitric oxide level and Plasma TNF-α level was done. Finally, radiological estimation and histopathology of tibio tarsal joints was performed. Statistical analysis was performed using one way ANOVA followed by Dunnet’s test at different p-values. Results: Phytochemical study revealed the presence of flavonoids, phenolic compound, saponins and carbohydrates. For different parameter mentioned above, anti-arthritic activity shown by prophylactic high dose test extract (200 mg/kg) was as potent as standard drug Indomethacin (10 mg/kg). The effect of Prophylactic low dose extract (100 mg/kg) and therapeutic high dose extract (200 mg/kg) was less than that of Indomethacin (10 mg/kg). Furthermore, Therapeutic low dose extract (100 mg/kg) was not effective. Conclusions: The obtained results indicate that Costus speciosus rhizome extract possess significant anti-arthrtic potential.
Keywords: Costus speciosus, Freund’s complete adjuvant, Rheumatoid arthritis, biochemical estimation, radiological examination.